A Preliminary study on the brooding habits of the "mud clam" Anodontia edentula (Linne' 1758). - Dequina, Ariane Gayle Martir
The mudclam, Anodontia edentula, is a commercially important bivalve that is a primary source of fishery to the local people of Guimaras. Due to its high market demand, the supply of this species is practically decreasing. Thus, it is important to study the reproductive biology, in particular, the brooding habits, of this clam. The basic information may be used in the proper resource management and conservation purposes., Monthly samples were collected from August to December. Out of 340 clams 36 showed brooding habits. Both male and female clams brood although more brooding females were observed than males. Brooding habit was exhibited by clams of varying size distribution. However, there was no significant relationship between the clam size the occurence of brooding. The juveniles were mostly found underneath the inner gills but a small number were also found in the mantle cavity. The presence of the juveniles in the gills indirectly supports the assumption of the availability of parental nourishment in this area. Each clam contained juveniles ranging in number 1 to 8. These juveniles had varying sizes and some showed advanced stages of development suggesting mud clams are sequential brooders. Brooding, which is a form of parental care and protection due to the harsh environment, may be very important in the survival of juveniles of this species.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
This is aimed to study the reproductive biology, in particular the brooding habits of the mud clam Anodontia edentula (locally known as imbaw)
Keywords: Mud clam; Anodontia edentula (Linne, 1758)